Impact of gender on the survival of patients with glioblastoma. Issue 6 (7th November 2018) - Tian, Minjie; Ma, Wenying; Chen, Yueqiu; Yu, Yue; Zhu, Donglin; Shi, Jingping; Zhang, Yingdong
Abstract : Background: Preclinical models have suggested a role for sex hormones in the development of glioblastoma multiforme (GBM). However, the impact of gender on the survival time of patients with GBM has not been fully understood. The objective of the present study was to clarify the association between gender and survival of patients with GBM by analyzing population-based data. Methods: We searched the Surveillance, Epidemiology, and End-Results database who were diagnosed with GBM between 2000 and 2008 and were treated with surgery. Five-year cancer specific survival data were obtained. Kaplan–Meier methods and multivariable Cox regression models were used to analyze long-term survival outcomes and risk factors. Results: A total of 6586 patients were identified; 61.5% were men and 38.5% were women. The 5-year cancer-specific survival (CSS) rates in the male and female groups were 6.8% and 8.3%, respectively ( P =0.002 by univariate and P <0.001 by multivariate analysis). A stratified analysis showed that male patients always had the lowest CSS rate across localized cancer stage and different age subgroups. Conclusions: Gender has prognostic value for determining GBM risk. The role of sex hormones in the development of GBM warrants further investigation.